Prevalence and Clinical Impacts of HIV-1 Intersubtype Recombinants in Uganda Revealed by Near-Full-Genome Population and Deep Sequencing Approaches - Lee, Guinevere Q. (AIDS, 2017)
OBJECTIVES: To estimate prevalence, examine time trends, and test for clinical correlates and outcomes associated with HIV-1 intersubtype recombination under a full-genome sequencing context in a rural community in Mbarara, Uganda, where HIV-1 subtypes A1 and D co-circulate. METHODS: Near-full-genome HIV-1 Sanger sequence data was collected from plasma samples of 504 treatment-naïve individuals, who then received PI or NNRTI-containing regimens and were monitored for up to 7.5 years. Subtypes were inferred by Los Alamos RIP 3.0 and compared with Sanger/REGA and MiSeq/RIP. “Non-recombinants” and “recombinants” infections were compared in terms of pre-therapy viral load, CD4 count, post-therapy time to virologic suppression, virologic rebound, first CD4 rise above baseline and sustained CD4 recovery. RESULTS: Prevalence of intersubtype recombinants varied depending on the genomic region examined: gag (15%), prrt (11%), int (8%), vif (10%), vpr (2%), vpu (9%), GP120 (8%), GP41 (18%), and nef (4%). Of the 200 patients with near-full-genome data, prevalence of intersubtype recombination was 46%; the most frequently observed recombinant was A1-D (25%). Sanger/REGA and MiSeq/RIP yielded generally consistent results. Phylogenetic tree revealed most recombinants did not share common ancestors. No temporal trend was observed (all p>0.1). Subsequent subtype switches were detected in 27 of 143 (19%) subjects with follow-up sequences. Non-recombinant versus recombinants infections were not significantly different in any pre- nor post-therapy clinical correlates examined (all p>0.2). CONCLUSION: Intersubtype recombination was highly prevalent (46%) in Uganda if the entire HIV genome was considered, but was not associated with clinical correlates nor therapy outcomes.